Design rectenna for wireless energy harvesting - Elmi Gure, Abdirahman (2015)
There is an increasing interest in energy harvesting. The rectenna, which is a combination of a rectifier and an antenna, is a device to harvest wireless energy in the air. This thesis is concentrated on the analysis, design and measurement of compact rectennas for Wi-Fi (RF) wireless energy harvesting applications. The objectives of this project is to study and design a 2.45 GHz rectenna to capture and convert microwave signal into DC power. Generally, rectenna introduces an overview of a rectifying antenna (rectenna) circuit topology for energy harvest. Specially, a rectenna based on a microstrip patch antenna and a microwave rectifier and both of them will determine the overall performance of rectenna. Rectenna was designed and simulated results were carried out by the microwave engineering professional design software’s, known as CST microwave studio and Advance Design System (ADS), All design and simulation results will be reported and fabricated on FR-4 board because the printed rectenna is low cost and easy to manufacture. Measurement experiment is carried on by transmitting different input power by using horn antenna and being measured at different load (100-400 Ω). Based on the experimental result, the maximum output voltage measure at the load is 0.47 mV for 200 Ω resistor and 15 dBm transmit input power and -17 dBm receive input power. The microwave to DC conversion efficiency of the rectenna was measured as 3.6 % for 200 Ω resistor with 15 dBm transmit input power and -17 dBm receive input power. This project is successfully proved that new energy could be harvest by using rectenna technology.